RISK-TAKING AND STUDENTS’ SPEAKING ABILITY: DO THEY CORRELATE? - Lilis Suryani; Ningtyas Orilina Argawati (STKIP Siliwangi, 2018)
The students’ speaking ability somehow depends on some psychological issues such as motivation, self-esteem, or risk-taking. This research aims at examining the correlation of students’ speaking skill especially with their level of risk-taking. The method used in this research is a quantitative research method with the correlational design. The Null hypothesis was “there is no correlation between Risk-taking and Speaking Ability”.The researchers used the speaking test and questionnaire about risk-taking as the instruments to gather the data. Before examining the correlation between those two variables, the normality test was conducted. The result showed that the data were in normal distribution so that the analysis was statistically continued using Pearson Product Moment. From the calculation, sig. 2-tailed of both risk-taking and speaking were 0.000 which was lower than the level of significance (0.05). It means that the Null hypothesis is rejected and the final result told that there is a correlation between Risk-Taking and Speaking Ability. While the Pearson correlation reached the point of 0.685 which means that the correlation between those two was large. Finally, we could conclude that risk-taking can be an issue to take into account choosing some methods of teaching speaking.